The Challenges Facing Teachers in Inclusion of Students with Special Needs at Jordanian Primary Schools from the Teachers' Point of View - Mohammad Abed Sakarneh (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aims to identify the most important challenges facing primary school teachers in integrating students with special needs in Jordan and to suggest solutions for them. The researcher used a qualitative research method for the data collection and analysis in addition to an interview technique. The sample consisted of ten teachers (5 males and 5 females) who taught students with learning disabilities, atusim spectrum disorders, sensory impairments or mild intellectual disabilities in primary schools.   The results of the study revealed that the most important challenges facing teachers in the inclusion process were infrastructure, resources, funding, classroom size, lack of time, lack of training and knowledge, lack of parents' involvement, evaluation and educational supervision and finally, attitudes towards inclusion of students with special needs. The researcher recommends to make more funding available to provide teachers with training needed for inclusion and the use of teaching technology with students, reduce the number of students in inclusive classrooms and enhance teachers' positive attitudes towards students with disabilities in primary schools.